The Effect of Financial Knowledge, Financial Skill, Financial Attitude, and Time Preference on Investment Intention With Perceived Risk as a Moderating Variable - Ratna Ningsih (CV. Civiliza Publishing, 2026)
This study aims to analyze the influence of Financial Knowledge, Financial Skill, Financial Attitude, and Time Preference on Intention to Invest with Perceived Risk as a moderating variable. The study was conducted on employees of Hospital X in Tangerang with a sample of 190 respondents. The post-COVID-19 pandemic conditions have driven changes in individual financial behavior, particularly in financial management and investment decision-making. This study used a quantitative approach with the Structural Equation Model (SEM) method. The results showed that Financial Knowledge, Financial Skill, Financial Attitude, and Time Preference significantly influenced Intention to Invest. In addition, Perceived Risk was proven to moderate the relationship between Financial Skill and Intention to Invest, but was unable to moderate the relationship between Financial Knowledge, Financial Attitude, and Time Preference on Intention to Invest. This study contributes to the development of financial behavior and investment literature, particularly regarding the role of financial knowledge, financial skills, financial attitudes, time preferences, and risk perception in shaping individual investment intentions. The findings of this study are also expected to form the basis for developing financial education and literacy to increase public participation in investment activities.